A study for Bacterial Infection in Acute Diarrhea Patients (Baghdad Science Journal, 2025)
500 samples of diarrhea stool were collected from different ages(less than 1year –upto30years) and for both genders from some patients in (Alwiya hospital for children, Al-kendi, central health public laboratory and some gavernarated labs) period(1/11/2009—1/10/2010). Kinds of bacteria and parasites agents were isolated and identified from patients with diarrhea.Nine species of gram negative bacteria from enterobacteriaceae were isolated, E. coli isolated are the higher ratio 4.8% of all, then Salmonella typhi4.6% while the lowest ratios is Citrobacterfreundii 0.4%, while the other identified species were be among the previous rotios. also Plesomonasshigelloides was isolated which concedride one of the bacterial local studies.many methods were depend on in order to identifiy; growth on media like (Enrichment ,differentials and differetials) media.Biochemical test represents with API20E, also. Some confirmed tests represent with a modern and important identical tools was used for first time to identify the entericbacteria, by (Rapid ID 32) usually used with mini API system where the results record automatically.